2013
DOI: 10.1016/s0140-6736(13)61030-2
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of intimate partner homicide: a systematic review

Abstract: WHO, Sigrid Rausing Trust, and the UK Economic and Social Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
495
0
48

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(586 citation statements)
references
References 23 publications
13
495
0
48
Order By: Relevance
“…Furthermore, it is likely that these estimates are conservative because of the quality of the information. Nevertheless, the 66 countries participating in the data gathering effort show that the main risk of homicide among women comes from their partner 19 . On the other hand, women who kill their partners normally act in self-defense.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is likely that these estimates are conservative because of the quality of the information. Nevertheless, the 66 countries participating in the data gathering effort show that the main risk of homicide among women comes from their partner 19 . On the other hand, women who kill their partners normally act in self-defense.…”
Section: Discussionmentioning
confidence: 99%
“…Common health consequences of IPV include: acute injuries (Sheridan & Nash, 2007), chronic diseases (Campbell, 2002), gynaecological problems (McCauley et al, 1995), and homicide (Stockl et al, 2013). While the physical effects of HIV could manifest only some time after transmission, HIV-infected people are more susceptible to opportunistic infections and experience sideeffects of chronic medication, especially if they are not virally supressed.…”
Section: What Are the Common Health Consequences?mentioning
confidence: 99%
“…Compared to men victimized by IPV, women are more likely to have serious injuries. [1][2][3] Of importance, more than one in 10 homicides is perpetrated by an intimate partner, and more than a third of female homicides are perpetrated by partners. 1 Even though several studies have shown higher prevalence rates of domestic violence among Latino populations as compared to other ethnic groups, 4,5 only scarce data on the subject are available in Latin America 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Of importance, more than one in 10 homicides is perpetrated by an intimate partner, and more than a third of female homicides are perpetrated by partners. 1 Even though several studies have shown higher prevalence rates of domestic violence among Latino populations as compared to other ethnic groups, 4,5 only scarce data on the subject are available in Latin America 4,6,7 . According to a recent WHO report, Brazil ranks seventh in female homicide rates among 84 countries of the world, surpassing most of its South American neighbors except Colombia, all European countries except Russia, and all African and Arabic countries.…”
Section: Introductionmentioning
confidence: 99%